ETIKA PROFESI PARIWISATA: PENGGUNAAN MEDIA SOSIAL SEBAGAI SARANA PROMOSI DESTINASI PARIWISATA - Febryola Indra; Cheryl Jocelyn; Felicia Andyny Harijanto; Feronia Aitana Iwantoro (Jurnal Inovasi Penelitian, 2023)
This article will explain the role of social media in promoting tourism destinations. In the digital era that has become more advanced, social media is considered as an effective factor in expanding the reach of tourism destination promotions. This research is research by collecting secondary data from various existing articles and journals related to the topics discussed. The analytical method used is a qualitative method by taking several other journal data sources to be interpreted in explaining the topic of this article. Then, this article will discuss the code of ethics for using social media correctly, how to promote tourist destinations with ethical social media, and the benefits of using social media as a means of promotion